A Study Using The Theory Of Planned Behaviour To Analyze Purchase Intention And Actual Purchase Towards Green Cosmetics In Pontianak - Mirhard, Yulia B1024141004 (Jurnal Manajemen Update, 2017)
The purpose of this research is to analyze Purchase Intention and Actual Purchase towards Green Cosmetics in Pontianak by using the Theory of Planned Behaviour as the awareness of global community towards environmental issues has been rapidly increasing. These days, the market for green product is expanding worldwide in a variety of industries, such as food, fashion and cosmetics. There have been huge increases in encouragement across the world to market natural cosmetic as customers are shifting back form chemical ingredients cosmetic to more natural cosmetics. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is consumers in Pontianak who are above 18 years old and used green cosmetics for the last six months. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: There is significant relationship between attitude and purchase intention, H2: There is significant relationship between subjective norms and purchase intention, H3: There is significant relationship between perceived behavioural control and purchase intention, H4: There is significant relationship between perceived behavioural control and actual purchase, H5: There is significant relationship between purchase intention and actual purchase. The result of this research shows that H1, H3, H5 are accepted but H2 and H4 are rejected.